Odpowiedź:
a)
(1 - 2sin²α)/sinαcosα = (1 - tg²α)/tgα
(cos²α - sin²α)/sinαcosα = (1 - tg²α)/tgα
cos²α/sinαcosα - sin²α/sinαcosα = ( 1 - tg²α)/tgα
cosα/sinα - sinα/cosα = (1 - tg²α)/tgα
ctgα - tgα = (1 - tg²α)/tgα
ctgα - tgα = 1/tgα - tg²α/tgα
1/tgα - tgα = 1/tgα - tgα
L = P
Równość jest tożsamościowa
b)
(sinα - sin³α)/cos³α + sin³α/(cosα - cos³α) = tgα
sinα(1 - sin²α)/cos³α + sin³α/[cosα(1 - cos²α)] = tgα
sinαcos²α/cos³α + sin³α/cossin²α = tgα
sinα/cosα + sinα/cosα = tgα
tgα + tgα ≠ tgα
L ≠ P
Równanie nie jest tożsamościowe
c)
1 + cos(π + α) + sin(π/2 - α) = cos²(π - α) + sin²(2π - α)
1 + cos(180° + α) + sin(90° - α) = cos²(180° - α) + sin²(360° - α)
1 - cosα + cosα = cos²α + sin²α
1 = 1
L = P
Równość jest tożsamościowa